(untitled) (Olhar de Professor, 2021)
This report aims to highlight the educational path and practices proposed for Early Childhood Education, early years of Elementary Education, Special Education and Youth and Adult Education - PHASE I, in Covid-19 times, in the Municipal Education Network of a city in the Northwest of Paraná state. The qualitative research investigated which teaching practices and methodological activities were adopted in the time frame from March to June 2020 in order to enable the continuity of educational experiences, respecting social distance and maintaining interaction. The comparison of the information collected made it possible to identify that among the methodological alternatives presented by the Ministry of Education and the State Secretariat of Education of Paraná as options to continue the educational process, the network opted for carrying out non-classroom activities. These activities were based on the elaboration of printed activity books, instructional videos to families and asynchronous interactions via WhatsApp, thus providing a greater number of students with access to educational practices and keeping the proximity of relationships more successfully than if only mediated by online platforms.